Target audience penetration by a healthy lifestyle promotion programme: results from the Kilkenny Health Project - Murray, Peter; Shelley, Emer; Daly, Leslie; Collins, Claire; Conroy, Ronan; Graham, Ian (Economic & Social Studies, 1995)
Between 1985 and 1992 County Kilkenny was the site of an evaluated programme of community intervention which aimed to reduce the population's heart disease burden by promoting the adoption of a healthy lifestyle. This paper analyses data on public awareness of the Kilkenny Health Project's activities collected in a 1990-91 evaluation survey. The implications of the findings for healthy lifestyle promotion programmes supporting the achievement of the targets set in the recently unveiled national health strategy are discussed.
Keywords: Lifestyle; Health surveys; Kilkenny Health Project; Heart disease